Effects of passion fruit (Passiflora tenuifila Killip) intake on eutrophic and obese subjects: Lipidomic approach. - Cardoso, Laila Guimarães Zeraik (2022)
Obesity and overweight result in metabolic changes that build up as risk factors for the development of the main non-communicable diseases. Among these alterations, dyslipidemia is an important risk factor for cardiovascular diseases (CDV) and is expressed in elevated plasma levels of triacylglycerols, cholesterol, and low-density-lipoprotein (LDL, VLDL) and decreased plasma levels of high-density lipoprotein (HDL). Passiflora tenuifila Killip is a native passion fruit species of the Brazilian Midwest region and is a good source of proanthocyanidins and dietary fibers. Proanthocyanidins are a class of phenolic compounds that are attributed with improving lipoprotein profile properties, translated as improved LDL/HDL ratio. Fibers are fermented by the gut microbiota and produce short-chain fatty acids (SCFA), also involved in the regulation of energetic metabolism.. A 30-consecutive-day-long intervention with lyophilized P. tenuifila flour was performed in eutrophic and obese subjects. Passion fruit ingestion increased fecal production of acetate, key SCFA in the modulation of lipid metabolism; reduced body fat percentage in all subjects; and reduced total cholesterol (TC) of subjects who presented basal CT > 130 mg/dL. After the intervention, plasma lipidomic analysis detected 44 statistically significant lipids, regardless of BMI. Considering the study population with altered TC, reduced levels of glycerophospholipids were observed, a lipid class studied for their involvement in CVD. The intake of P. tenuifila contributed to the improvement in cardiovascular risk markers and acts on lipid metabolism. These effects may be due to synergic action between the bioactive compounds in the fruit. Still, other studies are necessary to identify mechanisms related to the action of bioactives of P. tenuifila, which can be better directed by this lipidomic approach.